Practices supporting cue-based breastfeeding of preterm infants in neonatal intensive care units across Europe - Bente Silnes Tandberg; Hege Grundt; Ragnhild Maastrup; Annie Aloysius; Livia Nagy; Renée Flacking (International Breastfeeding Journal)
Abstract Background Emerging knowledge about supportive neurodevelopmental neonatal care shows the need for an individual approach to establish breastfeeding. However, evidence on how cue-based breastfeeding is supported in neonatal intensive care units (NICUs) is scarce. Therefore, the aim was to describe supporting practices for cue-based breastfeeding. Method Through Delphi rounds, a questionnaire was developed comprising questions on the usage and occurrence of supportive practices for cue-based breastfeeding. A multinational online survey was distributed September to October in 2023 to NICUs in Europe using snowball sampling. Practices such as the practice of skin-to-skin contact (SSC), restrictions for breastfeeding, providing information to parents, observing and responding to infants’ cues were explored. Results The survey was completed by 105 neonatal units across 15 European countries. Less than half (46%) of the NICUs had no restrictions upon placing the infant in SSC with the parents. Approximately half (49%) of the NICUs stated that infants had SSC within the first hour after birth. Many units (68%) had some restriction for breastfeeding. One week after birth, 48% of the NICUs encouraged breastfeeding for infants at 33 postmenstrual age whenever the infant showed cues, regardless of scheduled tube feeding time. This percentage increased to 59% at 33–35 gestational age. Less than half of the units (47%) stated that they had the necessary tools/instruments to support the transition from tube feeding to breastfeeding. There were variations in how milk intake was assessed, such as weighing before and after breastfeeding or estimating milk intake by time spent sucking. Infants in 50% of the units had to be fed exclusively orally before discharge. Many units (65%) provided specific support to or enabled discharge before the infant was exclusively orally fed. Conclusion European NICUs employ supportive practices, SSC, early initiation of breastfeeding, and provide information to parents. Staff plays a significant role in fostering cue-based feeding in preterm infant-mother dyads. There still exist restrictions for SSC and breastfeeding. To understand the impact of different strategies and practices, there is need for evaluations by parents and testing of the implementation of cue-based feeding practices in neonatal care.